THE PREVALENCE OF HEALTH RISK BEHAVIOURS AMONG PHYSIOTHERAPY STUDENTS IN THE WESTERN CAPE, SOUTH AFRICA - Frantz, Jose (Journal of Community and Health Sciences, 2020)
Introduction: Health professionals are key role players in health promotion. The question arises of what is the risk behaviour of physiotherapy students who in the future will play a major role in health promotion. Objective: To obtain baseline data on and to assess the prevalence of health risk behaviours of physiotherapy students. Method: A descriptive cross sectional quantitative study using a questionnaire adapted from the Youth Risk Behaviour Questionnaire. Participants: 332 physiotherapy students. Setting: Physiotherapy departments at universities in the Western Cape, South Africa. Intervention: Self-administered questionnaire on health risk behaviour. Results: The study found that there was a high prevalence of health risk behaviours among physiotherapy students and that knowledge alone did not influence changes in behaviour. Conclusion: The high prevalence of health risk behaviours among physiotherapy students in the current study however, indicates that knowledge alone does not influence behaviour. The study points out the need for physiotherapy programmes to equip students with more than just mere knowledge about health risk behaviours.